Reduction in energy consumption and operating cost in a dried corn warehouse using logistics techniques - Korrakot Y. Tippayawong (2018)
© 2013 by Maejo University, San Sai, Chiang Mai, 50290 Thailand. Corn is one of the major economic crops in Thailand. Corn postharvest operation involves various practices that consume a large amount of energy. Different energy conservation measures have been implemented but logistics consideration is not normally employed. In this work, attempt has been made to demonstrate that logistics techniques can offer a significant reduction in energy and cost. The main objective of this work is to identify and demonstrate possible approaches to improving energy efficiency and reducing operating cost for a dried corn warehouse operator. Three main problems are identified: (i) relatively high fuel consumption for internal transfer process, (ii) low quality of dried corn, and (iii) excess expenditure on outbound transportation. Solutions are proposed and implemented using logistics operations. Improvement is achieved using plant layout and shortest path techniques, resulting in a reduction of almost 50% in energy consumption for the internal transfer process. Installation of an air distributor in the grain storage unit results in a decrease in loss due to poor-quality dried corn from 17% to 10%. Excess expenditure on dried corn distribution is reduced by 6% with application of a global positioning system.